Ethnic Diversity and Social Integration—What are the Consequences of Ethnic Residential Boundaries and Halos for Social Integration in Germany? - Stefan Jünger; Merlin Schaeffer (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
Does immigration erode the social integration of contemporary mass-scale societies? Continued immigration and corresponding growing ethnic, racial, and religious diversity have prompted this important and highly controversial question. This article gives a~brief introduction to the scientific literature on this question and derives from it the following gap that it seeks to address: According to a~small number of studies on related but different topics, immigration may be detrimental to social integration if it physically manifests as one of two specific types of ethnic residential segregation. The contested boundaries hypothesis has it that border regions sandwiched between ethnically defined neighborhoods are particularly conflict prone and characterized by increased rates of crime. The halo-effect hypothesis claims that majority members who live in homogenous mainstream neighborhoods that border on ethnically diverse ones (or are even encircled by them) are more likely to vote for right-wing populist parties. In this article, we expand both approaches to the study of social integration in theoretical and empirical terms. With respect to theory building, we discuss why social integration, as indicated by social trust and community attachment, should suffer from these two types of ethnic segregation. To test these claims empirically, we use data from the geo-coded German General Social Survey (ALLBUS/GGSS) 2016 and 2018 that we merge with 100-m~ 100‑m spatial grid data from the German Census 2011. These data allow us to apply edge detection techniques to identify ethnic residential boundaries, and our recently developed donut-method to measure ethnic residential halos. To our knowledge our study is the first investigation into the arguably important question whether ethnic residential boundaries and halos erode social integration.
Keywords: 300; Ethnic heterogeneity; Ethnic conflict; Contact theory; Georeferenced survey data; Spatial analysis; Ethnische Diversität; Ethnischer Konflikt; Kontakttheorie; Georeferenzierte Umfragedaten; Räumliche Analyse